The New Operator Marching Method on Calculating the Electromagnetic Scattered Fields from the Periodic Structures (Communications in Computational Physics, 2019)
In this work, the operator marching methods based on the modifiedNeumann-to-Dirichlet (NtD) map are developed to calculate the scattered fields fromthe periodic structures, especially diffraction gratings with metallic material. For thegrating structures coated with the metallic material, the modified NtD map operatormarching scheme is numerically stable for calculating the electromagnetic scatteredfields. The modified NtD map operators are constructed by the integral equation(IE) method in each homogeneous medium of the layered medium structures, andavoid the blow up of the condition numbers from the challenging metallic materialwith the complex refractive index. For the calculations of the scattered fields fromthe diffraction grating structures, the modified NtD map operator marching methodtakes advantage of the periodic structure features, and avoids the calculations of thecomplicated quasi-periodic Green's function. Numerical results demonstrate that theproposed method achieves high accuracy and low computational workload for thescattered fields from both the dielectric and metallic diffraction grating structures.